Speed control of sensorless brushless DC motor by computing back EMF from line voltage difference - R. Sivakami; Thangaraj K. (International Journal of Advances in Applied Sciences, 2020)
Sensorless operation of permanent magnet brushless direct current (BLDC) motor drive controls the rotating speed with different applied voltage. No phase lagging is produced which leads to increase the efficiency and minimize the torque pulsation of the BLDC motor. Initially, motor can be started by following the v/f method then allows the sensorless mode after reaching the minimum speed of 500-1000rpm. The Sensorless BLDC motors are highly used due to higher efficiency, reliability power, acoustic noise, smaller, lighter, greater dynamic response, better speed versus torque characteristics, higher speed range and longer life. Thus the source voltage spikes and switching losses are reduced. This method can be demonstrated through MATLAB simulation and DSP TMS 320LF2407A is used in the experimental setup to get the output